"We are on the frontlines too": A qualitative content analysis of US social workers' experiences during the COVID‐19 pandemic. (6th August 2022) - Cederbaum, Julie A.; Ross, Abigail M.; Zerden, Lisa de Saxe; Estenson, Lilly; Zelnick, Jennifer; Ruth, Betty J.
Abstract: Social work has been a part of the essential workforce historically and throughout the COVID‐19 pandemic, yet lack recognition. This work explores the experiences and invisibility of social workers within the pandemic response. Data are drawn from a large cross‐sectional survey of US‐based social worker from June to August of 2020. A summative content analysis of responses to the question 'What do you wish people knew about social work during the COVID‐19 pandemic' was undertaken. Participants ( n  = 515) were majority white (72.1%) and female (90.8%). Seven coding categories were subsequently collapsed into three domains: (1) meeting basic needs, (2) well‐being (emotional distress and dual role) and (3) professional invisibility (workplace equals, physical safety, professional invisibility and organisational invisibility). Meeting social needs requires broad‐based policies that strengthen the health and social safety net. Social workers have and will continue to play a critical role in the response, and recovery from COVID‐19. Organisational and governmental policies must expand to increase the visibility and responsiveness to the needs of social care providers.